Needs Analysis of English for Tourism in Penyengat Island as a Heritage Trail - Afdal, Taufik; Mutiara Yulia Effendi (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This study seeks to investigate the needs and problems of tourism workers and students of English Education Department in using English for Tourism in Penyengat Island as a heritage trail. In this study, 13 respondents comprising university students, tourist guides and merchandise vendors were asked about their needs and problems with using the English for tourism. To collect the data, we distributed questionnaires related to the two indicators in need analysis; needs and interviews to collect the problems faced by tourism players. Then, the data were analyzed based on its medium and standard deviation. The results showed that most of the participants value speaking as the utmost important skill in tourism. Another skill viewed critical is listening. While reading, and writing were deemed as an additional skill that might boost their competitive values. The three most important purposes of the English language were to provide information, services, and assistance. Inappropriate words and idioms, a limited vocabulary, and a lack of grammar expertise were among the issues with English use.